(untitled) (World Bulletin of Public Health, 2022)
This article discusses treatments with angiogenesis inhibitors in the complex treatment of diabetic macular edema. A comparative analysis of all types of anti-VGEF drugs on macular edema is given. The use of brolucizumab is described in detail as the most optimal method among anti-VGEF drugs for the management of macular edema. It also provides the latest data with clinically confirmed data on the use of this drug.